2010
DOI: 10.1007/s12185-010-0678-6
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib followed by second allogeneic hematopoietic stem cell transplantation for relapse of Philadelphia chromosome-positive acute lymphoblastic leukemia after the first transplantation

Abstract: Although allogeneic hematopoietic stem cell transplantation (HSCT) is an established treatment for Philadelphia chromosome-positive acute lymphoblastic leukemia (ALL), the prognosis of patients who relapse after allogeneic HSCT has been extremely poor. Dasatinib, a second-generation tyrosine kinase inhibitor, is a promising agent for the treatment of Ph-ALL. We report on a Ph-ALL patient who relapsed early after the first allogeneic HSCT, but achieved complete molecular remission with dasatinib alone. She rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Under these circumstances, a second allo-HSCT might be considered. A case report 37 shows a positive outcome for a patient who received dasatinib followed by a RIC alloHSCT after imatinib and myeloablative alloHSCT failed to control the disease. All reports of alloHSCT show a very much less than ideal outcome in patients beyond CR1.…”
Section: Resistance To Tkis and Novel Agents For Use In This Scenariomentioning
confidence: 99%
“…Under these circumstances, a second allo-HSCT might be considered. A case report 37 shows a positive outcome for a patient who received dasatinib followed by a RIC alloHSCT after imatinib and myeloablative alloHSCT failed to control the disease. All reports of alloHSCT show a very much less than ideal outcome in patients beyond CR1.…”
Section: Resistance To Tkis and Novel Agents For Use In This Scenariomentioning
confidence: 99%
“…1,2 Based on improvements in efficacy and tolerability, next-generation TKIs have been widely used in first-line treatments for chronic myeloid leukemia (CML), 3,4 and dasatinib is used in second-line treatments for patients with Ph-pos ALL that failed to respond or were intolerant to imatinib 5 or another first-line agent. 6 Nilotinib is a TKI with a potent binding affinity for BCR-ABL1 tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported on the feasibility of inducing a second molecular CR with dasatinib in those who have experienced an early relapse NCCN Guidelines Insights CE after first allogeneic HCT, which allowed for a second allogeneic HCT. 48,49 Studies that include donor lymphocyte infusion (DLI) to induce further graftversus-leukemia effect in patients who experience relapse after allogeneic HCT have reported little to no benefit, although it has been suggested that this is due to an excessively high leukemic burden. 50,51 Published case reports have suggested that the use of DLI for residual disease or molecular relapse (as noted by levels of BCR-ABL fusion mRNA measured with PCR) after allogeneic HCT may eliminate residual leukemic clones and thereby prevent overt hematologic relapse.…”
Section: Hematopoietic Cell Transplantmentioning
confidence: 99%